Simulation on the effect of temperature on forward osmosis process across membrane - Nurulhidayah, Rosli (2013)
Forward Osmosis(FO)is one of the technologies that show a great performance in energy production and water supply. Forward osmosis is more preferred in both productions especially water supply because the purity of the water produce by forward osmosis technology is higher than other technology only by using low temperature,low pressure and low energy in the operation and also has low operating cost. The purposes of this research are to develop a process model program on forward osmosis process across the membrane and to use the develop model in order to investigate how the difference of temperature and concentration of draw solutions affects the forward osmosis process.The scopes of this research are more focus on the temperature where the range is from 20°C to 40°C, concentration of draw solution which is sodium chloride (NaCl) is from 1.0M to 2.5M and the type of membrane used is cellulose triacetate membrane (CTA).Besides,the simulation program is built based on the formulas adopted from a number of journals which are related to this research by using MATLAB software.By using the developed process model, the water purity produce was higher as the temperature and draw solution concentration increase. The results shown by the simulation are the same with the experiment result from other researcher.It shows both temperature and concentration has an important impact to water flux in forward osmosis process.Besides,this forward osmosis process model can be used as a foundation of the future research.